Modifikasi Fisik Sumber Pati Melalui Microwave Heat Treatment: Tinjauan Parameter Daya dan Waktu Terhadap Swelling Power dan Solubility Pati - Anisa Aulia Rahma; Dara Fazila Antugia; Christofer Lano Marus; Chantikha Dhevianna Mulia (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Physical modification of starch using microwave heat treatment (MHT) technology serves as an efficient and environmentally friendly alternative to enhance the functional properties of starch without chemical additives. This article aims to examine the influence of microwave power and heating duration on the swelling power and solubility of various starch types, including tapioca, taro, sago, and lotus rhizome. A review of four studies revealed that power and time parameters significantly affect the crystalline structure of starch granules, resulting in either enhancement or reduction of their functional properties. High power or prolonged heating may decrease swelling power due to crystal restructuring and granule disruption, while solubility increases as a result of amylose and amylopectin degradation. MHT has proven to accelerate the heating process in a volumetric and efficient manner, improving water absorption capacity and viscosity. Despite its drawback of uneven heat distribution, this method remains relevant as a physical modification technique aligned with green processing principles in the food industry.